Effect of Betahistine and Metformin on Antipsychotic-Induced Weight Gain: An Analysis of Two Clinical Trials - Kang, Dongyu; Jing, Zhihui; Li, Ranran; Hei, Gangrui; Shao, Tiannan; Li, Li; Sun, Mengxi; Yang, Ye; Wang, Ying; Wang, Xiaoyi; Long, Yujun; Huang, Xiansheng; et al. (Frontiers in Psychiatry, 2018)
Antipsychotic induced weight gain is one of the most common adverse effects of antipsychotic treatment. However, there is no well-established interventions for the weight gain yet. In this study, we pooled the data from two clinical trials, which were originally examining the efficacy of betahistine and the efficacy of metformin in treating antipsychotic-induced weight gain and insulin resistance. In total 67 people with schizophrenia or bipolar disorder treated with antipsychotics were assigned to 36mg day-1 betahistine (n=13) or 1000mg day-1 metformin (n=25) or placebo (n=29) for 12 weeks, with evaluation at baseline and week 12. The primary outcome was body mass index (BMI). After treatment, the metformin group had mean decrease in BMI of 1.46±0.14 (p<0.001), insulin resistance index (IRI) of 4.30±2.02 (p<0.001). The betahistine group had no significant alteration in BMI or IRI. However, the placebo group had mean increase in BMI of 1.27±0.77(p<0.001) and IRI of 0.45±0.86(p<0.001). Between two treatment groups, metformin significantly decreased weight, BMI, fasting glucose, insulin level and IRI but not waist circumference compared to betahistine. Moreover, metformin significantly decreased weight, BMI, waist circumference, fasting glucose, insulin level and IRI compared to placebo, while betahistine significantly decreased body weight, waist circumference, BMI, insulin level, IRI but not fasting glucose compared to placebo. In this study, we found that both metformin and betahistine treatment was efficacious in improving antipsychotic induced weight gain and insulin resistance, and metformin was more efficacious in preventing and revising the weight gain induced by antipsychotics.